Paraguay : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Annex on Paraguay analyzes the financial crisis of June 1997. The lingering effects of the 1995 financial crisis and the subsequent deterioration of performance of several Paraguayan domestic banks resulted in a new crisis in 1997. The paper highlights that 9.7 percent of private foreign currency deposits left the banking system during June 13 to July 18, 1997. This paper also examines the Southern Cone Common Market and its implications for Paraguay.